A Better Way to Manage Paediatric Maxillofacial Trauma; A Retrospective Study Examining the Presentation of Maxillofacial Soft Tissue Injuries and Management over 3-year period at a Regional Children's Hospital. Issue 1 (January 2022) - Chundoo, Shima; McMillan, Kevin; Williams, Rhodri
Abstract : Introduction: Maxillofacial treatment is evolving with changing paediatric lifestyles and clinical limitations, including COVID-19. The aim of this study is to assess trends in the presentation of maxillofacial soft tissue injuries and subsequent management within a regional paediatric hospital. Methods: Retrospective study over a 3-year period (from 2019-2021 between January and April). Inclusion of all paediatric patients seen on the emergency department by OMFS team. Results: Between 2019 and 2021, the total number of patients dropped by over half. The average age dropped from 5.9 in 2019 to 3.8 in 2021. Males were more commonly seen. Extraoral injuries increased by 21%. Intraoral injuries reduced by 8%. Less complicated communicating injuries and associated dental trauma were seen in 2021. Lip lacerations accounted for most injuries. In 2020, there was 21% reduction in conservative management of injuries. Wound closure under LA increased by 12% in 2020. There has been an overall increase in wound closure under GA by 5% between 2019 and 2020. Falls accounted for most injuries, however, there has been an increase in dog bite injuries by 5% in 2021. Conclusions: The average age has dropped between 2019-2021 and hence treatment options remain limited. Age, cooperation, and severity of injury are important factors. The number of overall lacerations has decreased but a greater proportion required formal closure under general anaesthesia. It is vital OMFS surgeons are aware of the changes in presentation and current trends in management. This will help to better equip surgical teams for the changing landscape of paediatric maxillofacial trauma.